The Use of Credit Ceilings in the Presence of Indirect Monetary Instruments : An Analytical Framework - Yossifov, Plamen (IMF Working Papers; Working Paper ;, 2002)
In this paper, we introduce credit ceilings in the standard model of the money multiplier and analyze their role in central bank's management of money supply in the presence of indirect monetary instruments. We show that under a regime of total credit ceilings, their optimal value equals the desired growth rate of the adjusted monetary base. Under a regime of partial credit ceilings, their optimal value depends on the desired growth rate of the adjusted monetary base, the degree of substitutability between the regulated and unregulated types of banks' earning assets, and the autonomous growth rate of the latter.